1988
DOI: 10.1152/ajpregu.1988.255.1.r61
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal endocrine dynamics during volume expansion in hypothyroid dogs

Abstract: To address the role of atrial natriuretic factor (ANF) in hypothyroidism in the control of cardiorenal-endocrine function during volume loading, the relationships between atrial pressure, ANF, the renin-angiotensin-aldosterone system, and renal hemodynamic and excretory function were examined during and after acute 10% body wt saline volume infusion in pentobarbital-anesthetized hypothyroid dogs (n = 8). Hormonal changes before and after thyroidectomy were also evaluated. Four to 6 wk after thyroidectomy, ANF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Bradley et al (26) reported in hypothyroid rats that a decrease in glomerular surface area due to growth retardation may contribute to the decrease of GFR. Data from hypothyroid animals showed an adaptive pre-glomerular vasoconstriction mechanism in response to a filtrate overload due to deficient sodium and water reabsorption in the epithelial cells of the proximal tubule (50). Additionally, a chloride load in distal tubuli of hypothyroid rats, caused by a disturbed activity of chloride channels CIC-2, activated the tubulo-glomerular feedback leading to decreased GFR (49).…”
Section: Impact Of Thyroid Hormones On Kidney Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Bradley et al (26) reported in hypothyroid rats that a decrease in glomerular surface area due to growth retardation may contribute to the decrease of GFR. Data from hypothyroid animals showed an adaptive pre-glomerular vasoconstriction mechanism in response to a filtrate overload due to deficient sodium and water reabsorption in the epithelial cells of the proximal tubule (50). Additionally, a chloride load in distal tubuli of hypothyroid rats, caused by a disturbed activity of chloride channels CIC-2, activated the tubulo-glomerular feedback leading to decreased GFR (49).…”
Section: Impact Of Thyroid Hormones On Kidney Growth and Developmentmentioning
confidence: 99%
“…Hypothyroidism is associated with a decrease in transporter function and the opposite occurs (7) decreased (7) Peripheral vascular resistance decreased (7) increased (7) RAS activity increased (17) decreased (17) RBF increased (49) decreased (48,49) Glomerular vasoconstriction decreased (53) increased (50,51) Glomerular surface area increased (48) decreased (26) Tubulo-glomerular feedback increased (54) increased (49) Filtration pressure increased (53) decreased (48) GFR increased (11,12) decreased (8-10) Proteinuria increased (7) increased (7) Activity of tubular ion transport increased (65,66) decreased (56,59) Tubular mass increased (64) decreased (49) Urine concentrating ability decreased (68, 69) decreased (48) CO = cardiac output; GFR = glomerular filtration rate; RAS = renin-angiotensin system; RBF = renal blood flow.…”
Section: Thyroid Disorders and Tubular Functionmentioning
confidence: 99%
“…Thyroid dysfunction may perturb liver function and vice-versa (4). In experimental animals, surgical or drug-induced hypothyroidism of a few weeks' duration has been shown to result in a decrease in GFR (6,7). However, clinical studies on hypothyroid subjects are very few and not much data is available on how hypothyroidism influences renal function in human beings.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In experimental animals, surgical or drug-induced hypothyroidism of a few weeks' duration has also been shown to result in a decrease in GFR. [5][6][7] However, the effect of hypothyroidism of short duration on GFR or serum creatinine level in humans has not been well documented.We retrospectively studied the prevalence of abnormally elevated serum creatinine level and the degree of its increase in patients who had undergone thyroidectomy for differentiated thyroid cancer and in whom thyroxine therapy was withheld for four weeks in preparation for radioiodine scanning/treatment. …”
mentioning
confidence: 99%
“…[1][2][3][4] In experimental animals, surgical or drug-induced hypothyroidism of a few weeks' duration has also been shown to result in a decrease in GFR. [5][6][7] However, the effect of hypothyroidism of short duration on GFR or serum creatinine level in humans has not been well documented.…”
mentioning
confidence: 99%